Quantitative analysis of surface enhanced Raman spectroscopy of Rhodamine 6G using a composite graphene and plasmonic Au nanoparticle substrate. (January 2017) - Goul, Ryan; Das, Susobhan; Liu, Qingfeng; Xin, Melisa; Lu, Rongtao; Hui, R.; Wu, Judy Z.
Abstract: A novel type of substrate for quantitative surface enhanced Raman spectroscopy (SERS) composed of chemical vapor deposition (CVD) graphene and in-situ fabricated rounded gold nanoparticles (AuNPs) was designed. SERS was measured on samples of different concentrations of Rhodamine 6G (R6G) on the AuNPs/graphene substrates using a low power 632.8 nm laser. Finite element simulations were carried out for a system of two gold hemiellipsoids under various conditions such as with R6G analyte covering the surface and with graphene underneath the nanoparticles. Graphene or R6G being present between the two nanoparticles caused a redshift in the plasmonic resonance frequency, and the graphene dampened the electric field of the surface. Regardless of the weakened electric field, the synergy of the AuNPs and graphene still enhanced the Raman signature of R6G to a greater extent than the nanoparticles or graphene alone could, which is attributed to the charge transferring mechanism effect of graphene on SERS. The lowest concentration of solid phase R6G deposited in this manner that could be detected was 8 × 10 −7 M. Higher analyte concentrations and the characteristic peak intensities of the analyte showed a logarithmic relation as anticipated from the plasmonically enhanced Raman scattering. Graphical abstract: